Powstawanie wad wrodzonych tarczy nerwu wzrokowego Część I. Embriologiczne i genetyczne aspekty rozwoju tarczy i nerwu wzrokowego - Wojtulewicz, Małgorzata; Marcinkiewicz, Władysław; Rękas, Marek; Kosatka, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Embryogenesis of the eye was presented and definite time of arising congenital anomalies of the optic disc, which characterized abnormal diameter disc, was determined on its background. As well genes, which control development of the optic disc were detailed.